2014
DOI: 10.4274/jcrpe.1471
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and Obesity in Children and Adolescents

Abstract: Obesity among children, adolescents and adults has emerged as one of the most serious public health concerns in the 21st century. The worldwide prevalence of childhood obesity has increased remarkably over the past 3 decades. The growing prevalence of childhood obesity has also led to appearance of obesity-related comorbid disease entities at an early age. Childhood obesity can adversely affect nearly every organ system and often causes serious consequences, including hypertension, dyslipidemia, insulin resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
177
0
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 429 publications
(225 citation statements)
references
References 102 publications
2
177
0
10
Order By: Relevance
“…Obesity during childhood/adolescence drastically increases the probability of obesity in adulthood [13,14]. Early-onset obesity is setting children up for a lifelong risk of obesity-associated complications, as it is now understood that early markers of adult cardiovascular disease begin in childhood [15].Obesity is associated with disorders of almost every system in the body [16]. For example, adults with obesity have increased incidence of cardiovascular disease, diabetes, high cholesterol, and hypertension [17][18][19].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Obesity during childhood/adolescence drastically increases the probability of obesity in adulthood [13,14]. Early-onset obesity is setting children up for a lifelong risk of obesity-associated complications, as it is now understood that early markers of adult cardiovascular disease begin in childhood [15].Obesity is associated with disorders of almost every system in the body [16]. For example, adults with obesity have increased incidence of cardiovascular disease, diabetes, high cholesterol, and hypertension [17][18][19].…”
mentioning
confidence: 99%
“…Obesity is associated with disorders of almost every system in the body [16]. For example, adults with obesity have increased incidence of cardiovascular disease, diabetes, high cholesterol, and hypertension [17][18][19].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in the number of overweight and obese children is indeed a major concern, because in small countries like Brunei Darussalam, 10% represents a significant proportion of the total population. Moreover, research has found that obesity at a young age is likely to persist into adulthood, which could lead to other chronic diseases (Güngör, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…prevelansı özellikle son 3 dekatta önemli ölçüde artmıştır (1,2) . Obezite çocukluk çağında ilk 1 yaşta, yaşamın 5.-6. yılında ve ergenlik döneminde belirgin bir artış göstermektedir.…”
unclassified